1981
DOI: 10.1073/pnas.78.12.7801
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin: regional distribution of the hormone and its binding sites in the human brain and pituitary.

Abstract: Immunoreactive calcitonin (CT), indistinguishable from human CT-(1-32) and its sulfoxide, has been identified in extracts of the hypothalamus, the pituitary, and the thyroid obtained from human subjects at autopsy. CT concentrations were highest in a region encompassing the posterior hypothalamus, the median eminence, and the pituitary; intermediate in the substantia nigra, the anterior hypothalamus, the globus pallidus, and the inferior colliculus; and low in the caudate nucleus, the hippocampus, the amygdala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(74 citation statements)
references
References 34 publications
2
71
0
1
Order By: Relevance
“…Calcr has been demonstrated in a variety of tissues not directly involved in the regulation of Ca 2+ homeostasis. Especially, expression of Calcr has been observed in the brain, suggesting that it has distinct functions also in the central nervous system (CNS) (Fischer et al 1981). In the CNS, calcitonin is thought to enhance the secretion of anterior pituitary hormones and inhibit appetite and gastric acid secretion (Pondel 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Calcr has been demonstrated in a variety of tissues not directly involved in the regulation of Ca 2+ homeostasis. Especially, expression of Calcr has been observed in the brain, suggesting that it has distinct functions also in the central nervous system (CNS) (Fischer et al 1981). In the CNS, calcitonin is thought to enhance the secretion of anterior pituitary hormones and inhibit appetite and gastric acid secretion (Pondel 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Like the CT receptor of other target cells or tissues, the placental CT receptor has a high affinity for salmon CT, the relative binding potencies of CTs derived from other species are maintained and non-related peptides do not bind. Furthermore, the placental receptor displays poorly reversible binding, characteristic of CT binding in all tissues studied [7,10,20,39,40].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent investigations have shown that the osteoclast [2][3][4][5] and renal tubular cells [6][7][8][9] are major target cells. Nevertheless, a number of other tissues possess CT receptors, including brain [10][11][12], lung [13], testes [14], and trout gill [15] as well as cell lines derived from a wide range of neoplasias including human breast [16], lung [17], and renal carcinoma [18], leukaemia [19,20], teratocarcinoma [21] and osteogenic sarcoma [22]. However, none of these has provided a substantial source of receptor because of either low specific binding activity, scarcity of tissue, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it has been shown to increase ACTH, ß-endorphin and cortisol serum levels (21), indicating a possible role in modulation of the anterior pituitary function, but this is challenged in other studies (22). Thirdly, specific binding sites for salmon calcitonin have been found in the brain of animals (23,24) and humans (25), suggesting a central intrinsic analgesic effect; supported by the successful use of calcitonin as a subarachnoid or epidural injection in humans (26). Finally, calcitonin has been shown to potentiate the analgesic effect of opioids in animals (27).…”
Section: Discussionmentioning
confidence: 97%